EXPLORING CHALLENGES IN UTILIZING ENGLISH RESOURCES FOR RESEARCH AND ITS REMEDIES - Fauza Nala Farhain; Yani Lubis; Deasy Yunita Siregar (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTThis qualitative study aimed to investigate students' problems in using English resources as research references at Universitas Islam Negeri (UIN) Sumatera Utara. Data were collected through observations, interviews, and focused group discussions (FGD). The instruments complementing the techniques include observation forms, interviews, and FGD question lists. Furthermore, the study used WhatsApp on a smartphone to record, confirm, and ensure the validity of data about the subjects. The findings showed that English department students at UIN Sumatera Utara had difficulties searching for research resources, understanding texts from international journals, and lacking skills in writing scientific papers. Therefore, intensive writing practices would enhance writing skills, perception, and knowledge of when to pursue assistance. It is recommended that the university establish an academic writing center and offer writing consultation. The center may regularly organize writing workshops to guide searching, using references, and structuring the manuscript.ABSTRAKPenelitian ini bertujuan untuk menginvestigasi permasalahan yang dihadapi oleh mahasiswa dalam menggunakan sumber-sumber berbahasa Inggris sebagai rujukan dalam penulisan karya ilmiah di Universitas Islam Negeri (UIN) Sumatera Utara. Penelitian yang menggunakan pendekatan kualitatif ini menggunakan berbagai tehnik pengumpulan data diantaranya observasi, wawancara dan Focus Group Discussion (FGD). Adapun instrumen yang digunakan dalam pengumpulan data adalah form observasi, daftar wawancara, dan daftar pertanyaan FGD. Untuk merekam proses wawancara, peneliti menggunakan Smartphone untuk merekam, mengkonfirmasi, dan memastikan validitas data tentang masalah yang diteliti. Hasil penelitian ini menunjukkan bahwa mahasiswa Pendidikan Bahasa Inggris di UIN Sumatera Utara mengalami kesulitan dalam menelusur sumber-sumber penelitian dan dalam memahami teks dari jurnal internasional, serta kurangnya keterampilan dalam menulis karya ilmiah. Oleh karena itu, praktek penulisan karya ilmiah secara intensif perlu dikembangkan untuk meningkatkan keterampilan menulis, persepsi mahasiswa, dan pengetahuan mahasiswa tentang kapan saatnya mereka membutuhkan bantuan penulisan. Universitas seyogyanya membangun sebuah pusat penulisan akademik dan memberikan konsultasi penulisan. Pusat penulisan akademik ini juga dapat menyelenggarakan workshop secara reguler dengan memberikan bimbingan dalam penelusuran dan pemanfaatan sumber-sumber referensi serta bimbingan penyusunan naskah karya tulis ilmiah. How to Cite: Farhain, F.N., Lubis, Y., Siregar, D. Y. (2023). Exploring Challenges in Utilizing English Resources for Research and its Remedies. IJEE (Indonesian Journal of English Education), 9(2), 1-22. doi:10.15408/ijee.v10i1.30517